COMMUNITY PARTICIPATION IN THE 2022 REGIONAL ELECTIONS IN BANDAR SETIA VILLAGE, PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY, NORTH SUMATRA PROVINCE - Stepani, Gabriella; Sitorus, Kapita; Ivanna, Julia (UIN Mataram, 2024)
The election of regional heads in Indonesia is a direct mandate of the reform movement in 1998. The election of regional heads is part of local democracy, which to realize good democracy, the implementation that can be carried out is the election of regional heads. This aims to channel the aspirations of the community to exercise their voting rights. The election of Regional Heads that is carried out directly can increase the participation of the community. However, it is not uncommon for many people to not care about the election of regional heads. Most of them are apathetic and do not find out about the future leader they will choose. This can happen because the prospective leaders promise a lot of things that can attract the attention of the public but are not implemented correctly. So that the community is disappointed and does not want to know anymore about how the leader will lead them in the future. This analysis is to find out the participation of the community in carrying out local democracy through the election of regional heads. This study uses a qualitative descriptive method. Qualitative research is an approach used to understand the phenomena experienced by the research subject, for example motivation, perception, action, and so on.